Effect of combination of nano brown anchovy (Stolephorus insularis) nanoparticles and calcium hydroxide on inhibition Streptococcus sanguinis biofilm formation - Yuanita, Tamara; Juniarti, Devi Eka; Nabilla, Tasya; Wiratno, Amelia Rahma; Tarigan, Shindyloken Juni Artha; Afifah, Anisa Nur; Setyabudi (Universitas Airlangga, 2023)
Background: Lactobacillus acidophilus and Aggregatibacter actinomycetemcomitans are gram bacteria that can cause various problems in the oral cavity so that materials that have antibacterial potency are needed. Calcium hydroxide, chlorhexidine, and sodium hypochlorite as antibacterial ingredients have disadvantages such as forming tunnel defects, causing dysgeusia, and damaging periapical tissue, so it is hoped that there will be natural materials as alternatives. The nano brown anchovy has fluor as the active compound which has the potential as an antibacterial agent. Purpose: To analyze the effect of antibacterial potency of nano brown anchovy (Stolephorus insularis) on Lactobacillus acidophilus and Aggregatibacter actinomycetemcomitans. Methods: This research is a laboratory experimental in vitro with the post-test only control group design. Brown anchovy is made into nano and diluted by dilution method into several concentrations. The direct contact method was used between some concentrations and the two bacteria. The values of MIC (Minimum Inhibitory Concentration) and MBC (Minimum Kill Concentration) were obtained by counting the number of bacterial colonies on Mueller Hinton Agar media. Bacterial colony growth was calculated manually in Colony Forming Units (CFU). Results: Antibacterial potency of nano brown anchovy on Lactobacillus acidophilus showed MIC results at 1.56% concentration and MBC at 3.125% concentration. Antibacterial potency of nano brown anchovy on Aggregatibacter actinomycetemcomitans showed MIC results at 3.125% concentration and MBC at 6.25% concentration. Conclusion: Nano brown anchovy has antibacterial activity on Lactobacillus acidophilus and Aggregatibacter actinomycetemcomitans.